White teacher - Paley, Vivian Gussin, 1929-2019. (Cambridge, Mass. : Harvard University Press, 2000)
Publisher's description: Vivian Paley presents a moving personal account of her experiences teaching kindergarten in an integrated school within a predominantly white, middle-class neighborhood. In a new preface, she reflects on the way that even simple terminology can convey unintended meanings and show a speaker's blind spots. She also vividly describes what her readers have taught her over the years about herself as a "white teacher."
Reprint with a new preface. Originally published: ©1979.
Print version record.
English.
eBooks on EBSCOhost
Keywords: African Americans -- Education (Elementary); Kindergarten -- United States; Classroom management -- United States; Écoles maternelles -- États-Unis.; Classes (Éducation) -- Conduite -- États-Unis.; EDUCATION -- Students & Student Life; EDUCATION -- Preschool & Kindergarten; African Americans -- Education (Elementary); Classroom management; Kindergarten; United States